POLLEN RECORDS FROM THE OLIGOCENE OF WESTERN INDONESIA AS THE EVIDENCES OF CLIMATE CHANGES - Eko Budi Lelono (Scientific Contributions Oil and Gas, 2017)
In Southeast Asia, Oligocene climate is well known to be represented by dry/ seasonal climate. However, it was reported possible appearance of wet climate period during the expantion of dry condition. This work is aimed to confi rm the Oligocene climate which occurred in western Indonesia. Climate change is useful to understand the Oligocene stratigraphy of Western Indonesia. This study uses cutting samples from off shore exploration wells situated in West and East Java and West Natuna as well as on-shore Central Sumatera and West Java. Samples are processed using standard preparation methods to produce suitable pollen assemblage for quantitative analysis.This study proves that the Oligocene sediments yield rich pollen assemblages including those of environment and climate indicators. Abundant fresh water algae of Pediastrum and Bosedinia in Early Oligocene indicates the appearance of lacustrine sediments. This sediment was formed under dry/ seasonal climate as marked by rich grass pollen Monoporites annulatus in the absence or rare occurance of rain forest elements. Mean while, Late Oligocene is characterised by common brackish elements to indicate shifting paleoenvironment into transition to shallow marine. The climate was changing into wetter condition as evidenced by high appearance of Dacrydium and Casuarina as well as other rain forest palynomorphs. The wettest climate probably occured in Java region which refl ected a wet climate fringe to the eastern margin of Sundaland prior to the collision of the Australian and Asian Plates at the Oligo-Miocene boundary. However, in general, dry/ seasonal climate is the rule for most of the Oligocene in Western Indonesia.